Haflah Tilâwat al-Qur’ân dalam Tradisi Masyarakat Kota Bima - Aminullah, Muhammad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
As a religious book, the Koran has long interacted with his people, even since he was there. The forms of interaction are seen in the tradition of making the Koran as an object of memorization (tahfîdh), writing (kitâbah), and interpretation studies (tafsîr). For the case in Indonesia, there Haflah Tilâwat al-Qur’ân in the tradition of people in Bima. A Haflah Tilâwat al-Qur’ân is an event in which the reciters gather to recite verses of the Koran by using the art of reading al-Qur’an. Implementation is left to the community which is then coupled with the traditions of the people who will be in the title, especially in the tradition of weddings and circumcisions. The interesting phenomenon is that after a reciter finished reciting verses of the Koran are the meaning and explanation of the content of the verse being read by a cleric. This article will explore the phenomenon of living Koran in the tradition of the Bima, how Haflah Tilâwat al-Qur’ân is held in the tradition of Bima’s community and society, and how Haflah Tilâwat al-Qur’ân is purported?